Conservative Kidney Management in the Middle East and North Africa: Attitudes, Practices, and Implementation Barriers - Sahar H. Koubar; Taha Hatab; Farah Abdul Razzak; Imed Helal; Ala Ali; Abdulhafid Shebani; Saleh Kaysi; David Gunderman; Akram Al-Makki; Sara N. Davison (Kidney International Reports)
Introduction: Conservative kidney management (CKM) is poorly developed and not easily accessible globally, especially in middle- and low-income countries. This study aimed to understand the perspectives of nephrologists on CKM and the barriers to its implementation in the Middle East and North Africa (MENA) region. Methods: We conducted an online survey. Nephrologists were contacted through their local nephrology societies. Responses were divided into the following 3 groups as per the country’s income classification by the World Bank: high-, middle-, and low-income. Results: A total of 336 surveys were analyzed (response rate: 34.28%). The mean age of participants was 43.3 ± 9.8 years; 50% were male, 91% practiced in urban settings, and 18% were affiliated with academic centers. Of the participants, 76% were from middle-income countries. Nearly 80% of the participants were aware of CKM, and 65% accepted CKM as a treatment modality for kidney failure. However, only 20% consistently offered CKM to their patients and only 16% had a formal CKM program at their institution. Among these, 12% had a multidisciplinary team and only 6% had formal CKM training. The major perceived barriers to CKM implementation were financial and resource constraints (37.7% and 32.7%, respectively). Cultural and religious barriers constituted 18.3% and 8.6%, respectively, and were similar among the 3 income groups. Conclusion: Despite the significant awareness of CKM in the MENA region, its implementation remains poor. Key barriers include financial limitations, resource shortages, and a lack of training. Regional and national research is required to address these challenges and guide policies to improve CKM accessibility and implementation.